Project Based Learning (PBL) Based Lesson Study for Learning Community (LSLC) in kindergarten - Sumarni, Sri; Putri, Ratu Ilma Indra; Andika, Windi Dwi (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
There is a gap in the learning approach applied by the teacher in stimulating early childhood math skills. This study aims to describe the Lesson Study for Learning Community (LSLC) application based on Project Based Learning (PBL) in the implementation of learning to stimulate children's mathematical abilities. The method used is descriptive qualitative in group B children in IT Fathul Ilmi Kindergarten Palembang. The result is that PBL-based LSLC has learning stages; plan, do, see, and redesign mathematics learning projects. These stages facilitate children to optimally master early mathematical abilities and develop interaction, communication, and cooperation, as well as the development of caring characters and empathy for friends in completing math projects together. The application of PBL-based LSLC makes learning in Fathul Ilmi Kindergarten active and interactive, so the PBL-based LSLC is recommended to teachers and stakeholders in early childhood mathematics learning.